(untitled) (Third Sector Social Economic Review, 2024)
In this research, for demand-based production, the North West Corner Method (NWCM), Vogel’s Approach Method (VOGEL), Minimum Cost Method (MCM), Stepping Stone Method (SSM) and Modified Distribution Method (MODİ) were used in production management. It is aimed to make and compare cost analyzes for internal logistics processes using models. According to the results obtained in the study, there are no statistically significant differences in terms of cost in the pairwise comparisons of NWCM, MCM and VOGEL methods (p>0.05). According to the results of comparing the main models with hybrid models other than their own hybrid models, the differences between MCM and NWCM-SSM, the differences between MCM and VOGEL-SSM, and the differences between VOGEL and NWCM-SSM are statistically significant (p <0.05). According to the results of the correlation analysis, there is a statistically significant relationship between cost, demand and method. According to the GLM analysis results, the parameters of NWCM, NWCM-MODİ, MCM, MCM-SSM and MCM-MODİ based on demand over cost. The effect is statistically significant. Although going beyond the current production system and a demand-oriented system causes additional costs, these costs can be made lower and bearable thanks to production management based on appropriate internal logistics selection. In this way, it is possible for businesses to gain advantages both in terms of competition and marketing.